Evolution of the unfolded protein response in plants. (2nd May 2021) - Howell, Stephen H.
Abstract: The unfolded protein response (UPR) in plants is elicited by endoplasmic reticulum stress, which can be brought about by adverse environmental conditions. The response is mediated by a conserved signalling network composed of two branches – one branch involving inositol requiring enzyme1‐ basic leucine zipper60 (IRE1‐bZIP60) signalling pathway and another branch involving the membrane transcription factors, bZIP17 and −28. The UPR has been reported in Chlamydomonas reinhardtii, a unicellular green alga, which lacks some canonical UPR signalling components found in vascular plants, raising the question whether C. reinhardtii uses other means such as oxidative signalling or Regulated IRE1‐Dependent Decay to activate the UPR. In vascular plants, IRE1 splices bZIP60 mRNA in response to endoplasmic reticulum stress by cutting at a site in the RNA that is highly conserved in structure and sequence. Monocots have a single IRE1 gene required for viability in rice, while dicots have two IRE1 genes, IRE1a and ‐b . Brassicas have a third IRE1 gene, IRE1c, which lacks a lumenal domain, but is required in combination with IRE1b for gametogenesis. Vascular and non‐vascular plants upregulate a similar set of genes in response to endoplasmic reticulum stress despite differences in the complexity of their UPR signalling networks. Abstract : The Unfolded Protein Response is an evolutionary conserved response to protect plants from adverse environmental conditions. The signaling network for this response has increased in complexity, and the response has taken on greater functions during the course of plant evolution.